SISTEM INFORMASI PENGELOLAAN STOK BARANG DAN HASIL PENJUALAN BERBASIS WEB PADA TOKO KOSMETIK CENDIA.: WEB-BASED STOCK MANAGEMENT INFORMATION SYSTEM AND SALES RESULTS AT CENDIA COSMETIC STORE - Mallisza, Danyl; Maulana, Afif (Jurnal Manajemen Teknologi Informatika, 2024)
The management of stock and sales results at the Cendia cosmetics store is still done manually, so there is often a buildup of documents and sales reports. With this system, it is hoped that the management of stock and sales results will be more effective and efficient so as to produce accurate reports. The research method used is by analyzing the current system and identifying needs using the system development life cycle (SDLC) with UML design tools. This information system was created to make the process of managing stock and sales results at the Cendia cosmetics store easier to be more effective and efficient because all data has been stored in database form and produces more accurate output reports on stock management and sales results as expected. The information system for managing stock and web-based sales results at the Cendia cosmetics store has been computerized so that it can save time and energy compared to the old system and stock management becomes more effective and efficient